Review of Supply Chain Integration Between 2000 and 2019:Analysis of Current Status and Future Trends - Gizem Erboz; Zoltan Szegedi (International Journal of Supply Chain Management, 2020)
Supply Chain Integration (SCI) integrates the activities between a firm and its channel members; therefore, it is a significant interdisciplinary subject for Supply Chain Management. The main aim of this paper is to review previous research on SCI in main academic sources to give some insights and practical information in the field of SCI, while indicating an overview of the main definitions, descriptive analysis and key themes of the selected studies. This paper refers to 115 research articles in 28 journals from main academic sources between 2000 and 2019. The main result of this study shows that in the last years, research interest in SCI has increased. Although there is a huge geographic dispersion on published studies, the USA holds a leading position on SCI publications. It has been identified that scholars mainly are looking forrelationship between SCI and performance issues; in addition,new themes emerge such as the implementation of Information Technology (IT) in order to have better-integrated Supply Chains. By considering the complexities of Supply Chains, this research contributes to the literature on the ways of analyzing new trends and geographical dispersion as well as identifying the key themes in the context of SCI.